Endoscopic repair of cerebrospinal fluid leaks - Mohammed, Ben Husien (Division of Neurosurgery, 2018)
Developmental Venous Anomalies are a normal variant that may be associated with other cerebral vascular malformation they have bean previously referred to Venous angiomas. DVAs are the most frequently encountered cerebral vascular malformation and their incidence is reported to be high as 2.6%. DVAs are classified into two types based on draining veins. Either deep or superficial. Those that drain into subependymal veins are classified as deep and those that drain into cortical pial veins are classified as superficial. The trans-cerebral veins join either the deep or superficial venous systems by crossing a varying length of the brain parenchyma. Controversy surrounds their exact clinical significance, as DVAs are rarely symptomatic. The symptoms displayed by a patient can be related to a lesion that is associated with DVAs, such as a cavernoma. Study Aim: To describe the patients presenting to a single unit over a 10-year period with symptoms attributable to a DVA. Results: Out of 19 patients in the database with the diagnosis of DVA, 10 were identified where the clinical presentation was directly related to the DVA. Seven of the patients presented with haemorrhage, 6 had parenchymal bleeds and one was intraventricular. Two patients had neurological deficit, 1 was transient and one was progressive. One patient had sudden severe headache with no evidence of haemorrhage on CT scan. The age range was from 14 to 55 with a mean of 32,7 years. Four patients were male and 6 were female. Of the patients that presented with haemorrhage only one had a fistula, three other patients with haemorrhage had evidence on DSA of stenosis of the large collector vein, In the remaining 3 patients no reason for the bleed could be detected. One patient presented with left hemianopia that resolved after several hours, DSA showed minimal caput medusa with delayed filling of the collector vein. The other patient that presented with progressive neurological deficit in the form of progressive leg spasticity and dysarthria, Angiography showed a large collecting vein that drains in the jugular bulb was stenosed. The last patient that presented with sudden sever headaches, with no haemorrhage identified on CT scan, On DSA there was early filling of the DVA veins compared to other cerebral veins and two prominent posterior communicating thalamoperforating vessels were seen. Conclusion: Developmental venous anomalies are the commonest vascular malformation, and are rarely symptomatic unless associated with a cavernoma. In patients that have symptoms linked to DVAs (Haemorrhage, neurological deficit, sudden sever headaches) overall they have a good outcome, and the deficit related to a DVA tend to improve overtime, except for one patient that we had in our group, the DVA draining the pons and the cerebellar hemisphere had a tight outflow stenosis, that lead to progressive neurological deficit. In general, the majority of DVAs that are symptomatic do well.